Multi agent‐based strategy protecting the loop‐based micro‐grid via intelligent electronic device‐assisted relays. Issue 19 (16th February 2021) - Karimi, Hamed; Fani, Bahador; Shahgholian, Ghazanfar
Abstract : Penetrating distributed generation units into the radial distribution networks has been making the protection schemes become ever so complex. The microgrid modes of operation have also increased this complexity. Moreover, the 'loop‐based microgrid' concept has made it extremely difficult or even impossible to utilise the available radial protection schemes. Although redesigning a new protection structure solves the problem, there should be an affordable way for surviving today's protection systems; accordingly, this study equips the ordinary overcurrent relays with intelligent electronic devices to act as an agent within a multi‐agent framework. Given these devices are equipped with an efficient communication infrastructure for industrial applications, named IEC 61850 standard, the proposed approach uses a communication‐based strategy, named token, to securely protect the system without any conflict in relays' operation. The simulation results prove the effectiveness of the proposed method for any DG's penetration, network configuration and fault location. This kind of flexible strategies can affordably differ the expensive protection system replacement in the future revolutionary network upgrades.